2021
DOI: 10.1787/c2c1d276-en
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence and employment

Abstract: This document, as well as any data and map included herein, are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name of any territory, city or area. 2  DELSA/ELSA/WD/SEM(2021)12 ARTIFICIAL INTELLIGENCE AND EMPLOYMENT Unclassified AcknowledgementsThis publication contributes to the OECD's Artificial Intelligence in Work, Innovation, Productivity and Skills (AI-WIPS) programme, which provides policymakers with new evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 25 publications
2
44
2
Order By: Relevance
“…These actions include: promoting transparency and requiring consent where AI tools are being used; ensuring that there is a human in the loop and giving individuals a right to contest automated decisions; guaranteeing privacy; and fighting bias and discrimination. 18 The discussion centres around the application of these policy actions to the matching sphere. For a broader discussion of recent policy developments on AI and the labour market more broadly, the reader is referred to Salvi del Pero, Wyckoffi and Vourc'h (2022 [1]).…”
Section: Transparency and Explainabilitymentioning
confidence: 99%
“…These actions include: promoting transparency and requiring consent where AI tools are being used; ensuring that there is a human in the loop and giving individuals a right to contest automated decisions; guaranteeing privacy; and fighting bias and discrimination. 18 The discussion centres around the application of these policy actions to the matching sphere. For a broader discussion of recent policy developments on AI and the labour market more broadly, the reader is referred to Salvi del Pero, Wyckoffi and Vourc'h (2022 [1]).…”
Section: Transparency and Explainabilitymentioning
confidence: 99%
“…The application of AI can help workers remove themselves from work that they dislike and give them more time to do things that they enjoy ( 22 ). It has been demonstrated that the long-term use of AI contributes to increased employment and reduced working hours ( 23 ). The destructive power of AI on future employment could be offset by continuous growth in productivity and real incomes ( 24 ).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…While other gig workers such as Uber drivers or DoorDash delivers must be geographically proximate to clients, "ghost work" can be done from anywhere. Many workers reside in OECD countries, but reporting has highlighted how the AI tools provided by a number of major companies such as Amazon and Google significantly rely on the efforts of workers in a number of non-OECD countries, including Venezuela, India or Indonesia, with less stringent labour standards (Fang, 2019[77]; Gent, 2019 [78]; Irani, 2016 [75]).…”
Section: Box 5 Labour Rights Concerns In the Development Of Ai Applic...mentioning
confidence: 99%